Genocidas ir rezistencija Nr. 44(2) - Pocius, Mindaugas; Tumavičius, Andrius; Staveckaitė-Notari, Ramona; Allanijazov, Turganbek; Banionis, Juozas; Kaczmarek, Ryszard; Lučinskas, Gintaras (Genocidas ir rezistencija, 2018)
Pilnas leidinys